The Influence of Quality And Value of Bittersweet By Najla On Muslim Customer Commitmen - Anggina Yusila Heryanto; Siti Padilah; Ahmad Nuh; Tina Nurdiani (CV. Ulil Albab Corp, 2024)
This study aims to analyze the effect of quality and value of Bittersweet by Najla products on Muslim customer commitment. In an increasingly competitive business context, understanding the factors that influence customer commitment is very important. The research method used is a quantitative approach with data collection through questionnaires distributed to 163 respondents. Data analysis was conducted using Structural Equation Modeling (SEM) technique to test the relationship between variables. The results showed that food quality and value of Bittersweet by Najla have a positive and significant influence on customer commitment. The conclusion of this study confirms that improving product quality and creating high value can increase Muslim customers commitment to the Bittersweet by Najla brand.